2013
DOI: 10.1371/journal.pone.0073094
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceramide and Glucosylceramide Metabolism Is Altered in Sporadic Parkinson's Disease and Associated with Cognitive Impairment: A Pilot Study

Abstract: BackgroundMutations in the gene coding for glucocerebrosidase (GBA), which metabolizes glucosylceramide (a monohexosylceramide) into glucose and ceramide, is the most common genetic risk factor for sporadic Parkinson's disease (PD). GBA mutation carriers are more likely to have an earlier age of onset and to develop cognitive impairment and dementia. We hypothesized that plasma levels of lipids involved in ceramide metabolism would also be altered in PD non-GBA mutation carriers and associated with worse cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 30 publications
9
153
1
2
Order By: Relevance
“…The current research adds to the growing body of clinical evidence that plasma sphingolipids may reflect central processes, either as by‐products of disease states in the central nervous system or as contributors to these disease states, or both (Assies et al., 2010; Demirkan et al., 2013; Hammad et al., 2012; Han et al., 2011; Mielke et al., 2011). Numerous studies have observed associations between peripheral sphingolipid concentrations and psychiatric symptoms (Demirkan et al., 2013; Mielke et al., 2013; Xing et al., 2016) as well as elevated concentrations of sphingolipids in the periphery of individuals with psychiatric disorders such as depression and posttraumatic stress disorder (Gracia‐Garcia et al., 2011; Hammad et al., 2012). Currently, little is known about the relationship between peripheral and central biomolecules such as sphingolipids.…”
Section: Discussionmentioning
confidence: 99%
“…The current research adds to the growing body of clinical evidence that plasma sphingolipids may reflect central processes, either as by‐products of disease states in the central nervous system or as contributors to these disease states, or both (Assies et al., 2010; Demirkan et al., 2013; Hammad et al., 2012; Han et al., 2011; Mielke et al., 2011). Numerous studies have observed associations between peripheral sphingolipid concentrations and psychiatric symptoms (Demirkan et al., 2013; Mielke et al., 2013; Xing et al., 2016) as well as elevated concentrations of sphingolipids in the periphery of individuals with psychiatric disorders such as depression and posttraumatic stress disorder (Gracia‐Garcia et al., 2011; Hammad et al., 2012). Currently, little is known about the relationship between peripheral and central biomolecules such as sphingolipids.…”
Section: Discussionmentioning
confidence: 99%
“…1) assayed in probes drawn from Parkinson patients and healthy controls. The assessment of lipid markers in the context of Parkinson's disease is based on evidence of an involvement of lipid regulation [15][16][17][18][19][20][21].…”
Section: Biomedical Data Setmentioning
confidence: 99%
“…Thus, the homeostasis of ceramide metabolism may be critical in regulating lifespan and age‐associated diseases (Cutler & Mattson, 2001; Rao et al ., 2007). Indeed, it has been increasingly recognized, from the cellular to human level, that perturbations in ceramide metabolism are associated with longevity (Yu et al ., 2012; Gonzalez‐Covarrubias et al ., 2013; Cutler et al ., 2014; Huang et al ., 2014) and the development and progression of many age‐related diseases including cancer (Alberg et al ., 2013), atherosclerosis (Ichi et al ., 2006), insulin resistance and diabetes (Holland et al ., 2007; Holland & Summers, 2008; Boon et al ., 2013), Alzheimer's disease (Mielke et al ., 2012), and Parkinson's disease (Mielke et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%